2013
DOI: 10.3109/21691401.2013.856014
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplatforms attached Schiff bases by condensation method; Investigation of glucose oxidase enzyme as biocatalysts

Abstract: We report a easy approach for the immobilization of glucose oxidase enzyme (GOx) on nanoparticles. Nanoparticles-modified polystyrene-ANH2 (PSA) with some salicylaldehyde derivatives were synthesized by means of condensation and investigated the enzymatic properties of GOx immobilized on there. Modified polystyrenes were characterized using IR spectra, gel permeation chromatography, and scanning electron microscopy. All the characteristics of the immobilized glucose oxidase (PSA-SalH)-GOx, (PSA-SalCH3)-GOx, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Similar to our previous results of the polymeric supports [27,28], it is considered that more reusability of particle capped double-ferrocene than other. The reusability results showed that the mediators (ferrocene) were attached strongly enough for use in the immobilization of reductase enzymes.…”
Section: Discussionsupporting
confidence: 73%
“…Similar to our previous results of the polymeric supports [27,28], it is considered that more reusability of particle capped double-ferrocene than other. The reusability results showed that the mediators (ferrocene) were attached strongly enough for use in the immobilization of reductase enzymes.…”
Section: Discussionsupporting
confidence: 73%
“…Covalent immobilization efficiencies of enzymes on modified RHS Fourier transform infrared spectroscopy (FTIR) was used to analyze the chemical characteristics of the modified RHS [24,25] and the spectral data evidenced the covalent immobilization of BSA protein on GDA-linked RHS (Supplementary Figure S1). The immobilization efficiencies of the enzymes are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] The azomethine group, –CHN–, has sp 2 hybridized orbital, and the hybridized orbital of nitrogen atom in the azomethine group is biologically significant which is involved in many different biological processes such as decarboxylation, transamination, and electron transfer. [ 2 ] Recently, metal complexes of Schiff base have been gaining interest in bioinorganic chemistry because many of these complexes provide biological synthetic models in understanding the structure of biomacromolecules such as DNA, protein, metalloprotein, and enzyme in biological systems. [ 3 ] Hemoglobin and hemocyanin have been modelled by many Schiff base complexes which naturally occurring dioxygen carriers and storage proteins contain a transition metal ion.…”
Section: Introductionmentioning
confidence: 99%